Ectopic endometriotic stromal cells‐derived lactate induces M2 macrophage polarization via Mettl3/Trib1/ERK/STAT3 signalling pathway in endometriosis. Issue 3 (18th October 2022) - Gou, Yanling; Wang, Han; Wang, Tong; Wang, Hongli; Wang, Beidi; Jiao, Na; Yu, Yangyang; Cao, Yingying; Wang, Honglin; Zhang, Zongfeng
Abstract: Endometriosis is a gynaecological condition characterized by the growth of endometrium‐like tissues within and outside of the pelvic cavity. Recent studies have demonstrated that aberrant infiltration of M2 macrophages is mainly responsible for the establishment of endometriotic lesions. A growing body of evidence shows that glycolysis and lactate accumulation have great impact on the regulation of immunomicroenvironment. However, the communication signal between glycolysis and macrophages is poorly defined in endometriosis. Hereby, we investigate the correlation between glycolysis and M2 macrophage infiltration in endometriosis. Next, we confirm that lactate is pivotal factor that drives macrophage M2‐polarization to promote endometriotic stromal cells invasion in vitro and in vivo. In addition, we also identify that the activation of Mettl3 and its target gene Trib1 promote M2 macrophage polarization. Moreover, we also demonstrate that Trib1 induce M2 macrophage polarization via the activation of ERK/STAT3 signalling pathway. Finally, by injecting 2‐DG into endometriosis mice model, we show that the restrain of glycolysis significantly reduces the progression of endometriosis, which provides evidence for lactate as a potential therapeutic strategy for the prevention and treatment of endometriosis. Abstract : Aberrant infiltration of M2 macrophages and glycolysis both play an important role for the establishment of endometriotic lesions. However, the communication signal between glycolysis and macrophages is poorly defined in endometriosis. Therefore, we investigated the correlation between glycolysis and M2 macrophage infiltration in endometriosis and explored the underlying potential mechanism.